Implementasi Pencatatan Aliran Kepercayaan dalam Administrasi Kependudukan berdasarkan Putusan Mahkamah Konstitusi Nomor 97/PUU/XIV/2016 tentang Pengujian terhadap Undang-undang Administrasi Negara - Audinda Salsabila Mondya; Nurul Chotidjah (Bandung Conference Series: Law Studies, 2022)
Abstract. Religion and belief systems are conceptions of divine teachings that citizens have the right to believe in. In Law no. 39 of 1999 concerning Human Rights. The main provisions of this law in Article 22 paragraphs 1 and 2 emphasize that everyone is free to embrace their own religion and to worship according to their religion and beliefs. Believers in administrative or social life still experience discriminatory things. In Law no. 24 of 2013 concerning Population Administration still does not guarantee the rights of believers by leaving the religion column blank in civil registration. This is contrary to the 1945 Constitution, the Constitutional Court issued the Constitutional Court Decision No. 97/PUU-XIV/2016 concerning Examination of the State Administration Law. After the Constitutional Court's decision was enforced to date, there are discrepancies in these policies that affect policies in the City of Cimahi. Therefore, this study aims to determine the implementation of the registration of beliefs in population administration based on the Constitutional Court's Decision No. 97/PUU/XIV/2016 concerning the Testing of the State Administration Law, Case Study of the City of Cimahi.The research method used is normative juridical law research, data sources and data collection techniques using secondary data sources consisting of primary, secondary and tertiary legal materials. The inhibiting factor for the realization of the Constitutional Court's Decision in the Disdukcapil City of Cimahi is the difference in the implementation of implementation policies. The Constitutional Court's decision listed believers in the KTP but the Cimahi City Disdukcapil in the Religion column was deleted and changed to the Trust column. The Dukcapil of Cimahi City regulates the recording of adherents of a belief in Cimahi City through Circular Letter Number 471.14/ 10666/ Dukcapil concerning the issuance of Family Cards for Believers in God Almighty. Abstrak. Agama dan aliran kepercayaan merupakan konsepsi ajaran ketuhanan yang berhak diyakini oleh warga negara. Dalam UU No. 39 Thn 1999 tentang HAM. Pokok pengaturan dalam undang-undang ini dalam Pasal 22 ayat 1 dan 2 menegaskan bahwa setiap orang bebas memeluk agamanya masing-masing dan untuk beribadat menurut agamanya dan kepercayaannya. Penghayat kepercayaan pada kehidupan administrasi ataupun sosial masih mengalami hal bersifat diskriminatif. Dalam UU No. 24 Thn 2013 tentang Administrasi Kependudukan masih belum menjamin hak penghayat kepercayaan dengan dikosongkannya kolom agama dalam pencatatan sipil. Hal ini bertentangan dengan UUD 1945, MK mengeluarkan Putusan MK No 97/ PUU-XIV/2016 tentang Pengujian Terhadap UU Administrasi Negara. Setelah Putusan MK diberlakukan hingga saat ini terdapat ketidak selaras dalam kebijakan tersebut yang memengaruhi kebijakan di Kota Cimahi. Maka dari itu penelitian ini bertujuan untuk mengetahui Implementasi Pencatatan Aliran Kepercayaan Dalam Administrasi Kependudukan Berdasarkan Putusan MK No 97/PUU/XIV/2016 Tentang Pengujian Terhadap UU Administrasi Negara Studi Kasus Kota Cimahi. Metode Penelitian yang digunakan adalah penelitian hukum yuridis normative, sumber data dan teknik pengumpulan data yang menggunakan sumber data sekunder yang terdiri dari bahan hukum primer,sekunder dan tersier. Faktor penghambat terealisasikannya Putusan MK di Disdukcapil Kota cimahi perbedaan implementasi kebijakan implementasi. Putusan MK mencantukan penghayat kepercayaan di KTP tetapi Disdukcapil Kota Cimahi dalam kolom Agama dihapus dan diubah menjadi kolom Kepercayaan. Dukcapil Kota Cimahi mengatur pencatatan penghayat aliran kepercayaan di Kota Cimahi melalui Surat Edaran Nomor 471.14/ 10666/ Dukcapil tentang penerbitan Kartu Keluarga bagi Penghayat Kepercayaan Tuhan Yang Maha Esa.